Pengaruh Serbuk Cangkang Kerang Terhadap Kuat Tekan Bebas Tanah Lempung Lunak Pesisir - Dyah Pratiwi Kusumastuti; Yulita Arni Priastiwi; Anik Sarminingsih (Department of Civil Engineering, Diponegoro University, 2025)
As an archipelagic country, Indonesia has extensive coastal areas that are intensively developed for infrastructure. Kosambi District in Tangerang Regency is one of the rapidly growing coastal regions due to its proximity to Soekarno–Hatta International Airport. However, the area is predominantly underlain by soft marine clay soils with low bearing capacity and high compressibility, which pose challenges for infrastructure development. To improve soil stability, soil stabilization methods are required to enhance unconfined compressive strength and undrained shear strength. This study aims to analyze the effect of cockle shell powder addition on the unconfined compressive strength and undrained shear strength of soft marine clay. Laboratory tests were conducted on untreated soil and soil stabilized with 5%, 10%, 15%, and 20% cockle shell powder by dry weight of soil. The results indicate that the optimum performance was achieved at a 10% addition, resulting in a 24.86% increase in unconfined compressive strength compared to untreated soil. In addition to improving strength, the addition of cockle shell powder reduced water content and enhanced interparticle bonding, thereby improving soil stability. These findings demonstrate that cockle shell powder has strong potential as an effective stabilizing material for soft coastal clay soils.